Natural history of the mistletoe-feeding Thereus lomalarga (Lepidoptera, Lycaenidae, Eumaeini) in Colombia - Heredia, María Dolores; Robbins, Robert K. (Zootaxa, 2016)
The natural history and morphology of the immature stages of the butterfly Thereus lomalarga Robbins, Heredia & Busby are described and illustrated. The food plant is Oryctanthus alveolatus (H.B.K.) Kuijt (Loranthaceae). Chaetotaxy of the first instar is described and compared with that of three locally studied Thereus species. Larvae have four instars, and the dorsal nectary organ becomes functional in the third instar. They are facultatively tended by ants belonging to seven genera that are attracted to O. alveolatus by floral disc nectaries, honeydew producing Hemiptera, and secretory wounds produced by Hemiptera on the fleshy inflorescence rachis. The average period from egg to eclosion under lab conditions was 35.68 days. Females emerged before males. Adults of both sexes feed on nectar from the flowers of the food plant and on hemipteran secretions; adults were not observed feeding on other flowers. Campopleginae and Chalcidinae were the most important parasitoids.